Representation of an algebra associated with the Dynkin graph E_7 - Ostrovskii, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We describe the structure of pairs of self-adjoint operators A and B whose spectra belong to the set {±1/2, ±3/2} and for which (A+B)^2 = I. Such pairs of operators determine a representation of a *-algebra A_E_7 associated with the extended Dynkin graph E_7.